Penetapan wali adhol dalam perspektif hukum Islam dan hukum positif - Sholihah, Faridatus; Yuliardy Nugroho, Irzak (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2024)
One of the pillars of marriage is having a guardian on the part of the prospective bride, but in reality not all lineage guardians are willing to marry off their daughters, guardians who are reluctant to marry are called adhol guardians. This article will examine the case of determining an adhal guardian in the Kraksaan Religious Court case decision Number: 0078/Pdt.P/2020/PA.Krs. This research aims to determine the legal status of adhol guardians according to Islamic law and positive law, and to determine the factors that cause applications for adhol guardians at the Kraksaan Religious Court. The research method used is qualitative/field research (field research) where this research is descriptive. The data collection method was carried out through observation and interviews. The data sources used come from primary data and secondary data. The data analysis used is qualitative data analysis with an inductive thinking approach. Based on the results of the research, it was concluded that the legal status of the adhol guardian according to Islamic law and Positive law is valid, based on Islamic law, namely paying attention to qoidah fiqhiyyah and also in the 24th letter of the Al-Nur verse 32 of the Al-Qur'an there is an order to marry men and women who alone is worthy of marriage. And based on positive law, namely Law Number 1 of 1974 concerning marriage, article 23 of the Compilation of Islamic Law. The main factor is that many people apply for adhold guardians at the Kraksaan Religious Court because fathers as lineage guardians are reluctant to marry off their daughters for various reasons.